BUDIDAYA ARWANA DI DANAU LINDUNG EMPANGAU PERSPEKTIF EKONOMI ISLAM DESA EMPANGAU KECAMATAN BUNUT HILIR KABUPATEN KAPUAS HULU - Beni Supriadi (Adisam Publisher, 2024)
This research is motivated by the existence of arowana cultivation in the protected lake in Empangau Village which has made a significant contribution to the surrounding community, especially in managing the conservation of protected lakes and arowana fish. In order to maintain the safety of arowana fish and preserve the protected lake, it was jointly decided to maintain the security of the protected lake area. Meanwhile, the community also has other jobs to fulfill their daily needs. To overcome this problem, the community agreed to form an organizational structure for managing the protected lake. This research uses a qualitative approach and descriptive research type, data collection techniques and interviews, observation and documentation. The research results show that Arowana Cultivation in the Empangau Protected Lake from an Islamic Economic Perspective has carried out very good planning, organizing implementation and periodic evaluation because of the role of the Lake Management who are members of the organizational group in Nanga Empangau Village. The importance of cultivating Arowana in the Empangau Protected Lake makes the public aware of always calling for the preservation of the Protected Lake, especially keeping the lake sustainable forever.